Spatiotemporal Characteristics of HF‐Induced Ionospheric Turbulence Revealed by Diagnostic Stimulated Electromagnetic Emission and Test Radio Waves at HAARP. Issue 12 (21st December 2018) - Sergeev, E. N.; Grach, S. M.; Shindin, A. V.; Mishin, E. V.; Bernhardt, P. A.; Briczinski, S. J.; McCarrick, M.
Abstract: This paper describes the dynamic characteristics of ionospheric plasma turbulences excited by high‐power high‐frequency radio waves during ionospheric modification experiments at the High‐frequency Active Auroral Research Program heating facility, Gakona, Alaska. The data come from measurements of high‐frequency‐induced stimulated electromagnetic emission (SEE) and anomalous absorption of test radiowaves. In addition to quasi‐continuous pump (QCP) waves that excite the "standard" SEE, short pulses of diagnostic waves at frequencies shifted from the QCP frequency have been injected to generate diagnostic SEE. This experimental setup allowed us to study the spectra and damping rates of the plasma waves related to both diagnostic and QCP waves, as well as the QCP‐related small‐scale magnetic field‐aligned irregularities at different altitudes, ±25 km around the center of the heated volume. The results of numerical simulations of the upper hybrid‐related SEE and diagnostic SEE under a "double‐transformation" scheme with the use of an empirical model of the irregularities' spatial spectrum and its dynamics are in good agreement with the observations. Key Points: Artificial ionospheric turbulence dynamics is studied at the High‐frequency Active Auroral Research Program facility Altitude size of the region occupied by pump‐induced small‐scale striations and their scales across the geomagnetic field are estimated Damping rates of pump‐induced Langmuir and upper hybrid waves are determined